Expression of beclin 1 in primary salivary adenoid cystic carcinoma and its relation to Bcl-2 and p53 and prognosis - Jiang,L.C. (2014)
Beclin 1 plays a critical role in autophagy and functions as a haploinsufficient tumor suppressor. The expression and prognostic significance of beclin 1 in head and neck adenoid cystic carcinoma (ACC) are largely unexplored. Therefore, we investigated the expression of beclin 1, Bcl-2, and p53 in head and neck ACC tissue. Tissue samples from 35 cases (15 females, 20 males) of head and neck ACC were utilized for immunohistochemistry. Beclin 1 expression was observed in 32 cases (91.4%) and considered to be high in 15 cases (42.9%) and low in 20 cases (57.1%). Beclin 1 expression was significantly correlated with a histological growth pattern (P=0.046) and histological grade (P=0.037). Beclin 1 expression was inversely correlated with Bcl-2 expression (P=0.013) and significantly associated with overall survival (P=0.006). Bcl-2 and p53 expression were observed in 21 cases (60.0%) and 16 cases (45.7%). Bcl-2 expression was significantly correlated with perineural invasion (P=0.041) and not associated with overall survival (P=0.053). p53 expression was directly correlated with beclin 1 expression (P=0.044). Our results indicated that beclin 1 may be a novel, promising prognostic factor for clinical outcome in head and neck ACC patients and may play a part in the development of head and neck ACC by interacting with Bcl-2 and p53.